Evaluasi Efektivitas Program Modal Berkah OK OCE Indonesia Terhadap Keberlangsungan UMKM di Jakarta - Fira Vanka Lintang Kusuma; Ari Saptono; Herlitah (Indo Publishing, 2025)
This research aims to evaluate the effectiveness of the Modal Berkah program organized by OK OCE Indonesia on the sustainability of micro, small, and medium enterprises (MSMEs) in Jakarta. The evaluation is conducted using the CIPP model (Context, Input, Process, Product) to assess the background of the program implementation, availability of resources, conduct of activities, and the results achieved. This study employs a mixed-method approach with data collection through questionnaires, interviews, and observations. Respondents in this study consist of MSME actors who are participants in the program as well as the organizers. The results show that the Modal Berkah program is quite effective in providing access to capital and basic entrepreneurship training. However, there are still shortcomings in the aspects of ongoing assistance and sustainability evaluation of the businesses. Therefore, this program is considered to have a positive impact on the sustainability of MSMEs. However, there needs to be an enhancement in the process and follow-up to ensure that the program results can be optimally sustainable.